A survey of libraries in the United States - Bostwick, Arthur E.; Thompson, C. Seymour (American library association, 1926)
v. 1. Administrative work: pt. I. Public libraries. pt. II. College and university libraries.--v. 2. Service to readers: pt. I. Circulation and reference work in public libraries. pt. II. Service to readers in college and university libraries. pt. III. State legislation concerning public libraries.--v. 3. Public library service to children. Extension work and community service of public libraries. School library organization and service.--v. 4. Classification and cataloging. Inventory. Insurance and accounting. Binding and repair. Buildings and equipment. Index to vol. I-IV.